Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Aiaa Aviation 2021 Forum 2021
DOI: 10.2514/6.2021-2111
|View full text |Cite
|
Sign up to set email alerts
|

Trailing-edge serrations: improving theoretical noise reduction models

Abstract: This paper discusses the elements that make up a theoretical model for predicting the noise generated by a serrated trailing edge, and in particular, the required input to such a model; the wavenumber frequency spectra of the turbulence at the edge. It is proposed that this input, which is often modeled empirically, varies between a straight edge and a serrated edge and this fundamental difference in turbulence structure at the trailing edge leads to inaccurate theoretical predictions of noise reduction. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The scheduled experiments at the SWT investigated the trailing edge noise (Amiet 1976;Brooks, Pope, and Marcolini 1989) generation of a NACA0012 airfoil (Ayton et al 2021). This study was a collaborative work between VT, University of Southampton (UK) and University of Cambridge (UK).…”
Section: Introductionmentioning
confidence: 99%
“…The scheduled experiments at the SWT investigated the trailing edge noise (Amiet 1976;Brooks, Pope, and Marcolini 1989) generation of a NACA0012 airfoil (Ayton et al 2021). This study was a collaborative work between VT, University of Southampton (UK) and University of Cambridge (UK).…”
Section: Introductionmentioning
confidence: 99%
“…Among other authors, Guérin et al [1] showed that a satisfactory agreement can be reached when those isotropic turbulence spectra are used to predict rotor-stator-interaction noise. Trailing edge noise is caused by the interaction of boundary layer turbulence with the trailing edge of an airfoil and the critical ingredient for its prediction is the wall surface pressure autospectrum near the trailing edge, as Ayton et al [2] have also recently discussed in their paper. In contrast to the transverse velocity spectrum associated with leading edge noise, no comparable consensus exists within the scientific community for modeling the wall surface pressure autospectrum associated with trailing edge noise.…”
Section: Introductionmentioning
confidence: 99%